Analysis of co-working space needs as an alternative learning environment for students - Raudotussolehah, Rika Mia; Rakhmat, Cece; Budiman, Nandang; Masya, Hardiyansyah (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2024)
Co-working spaces, which were initially favored by freelancers and startups, are now starting to be eyed by students as a suitable place for alternative learning. This study involved a sample of Postgraduate students at the Masters and Doctoral levels from one of the Universities in Bandung. The purpose of this study was to see what students wanted from a collaborative workplace or co-working space as an alternative learning place. The data collected includes student preferences for facilities, atmosphere, and time flexibility offered by co-working spaces. The results of the study show that students in the midst of their busy learning activities really need a supportive place, the majority of students consider co-working spaces as a more productive place to study. This choice is influenced by several factors, including convenience, fast internet access, an environment that supports collaboration, and the existence of supporting facilities such as discussion rooms and the availability of food that can be ordered. These findings indicate that there is great potential to build a student-friendly workplace